1999
DOI: 10.1021/ac9907585
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Diffusion Coefficient Distributions in Humic and Fulvic Acids by Means of Diffusion Ordered NMR Spectroscopy

Abstract: The use of the computer program CONTIN to analyze pulsed-field gradient NMR (PFG-NMR) data for several standard humic and fulvic acids is described. An advantage of PFG-NMR analysis is that integration of different spectral regions provides a picture of how the diffusion coefficients vary with functional group composition for a given sample. Using prior knowledge of the sample and the principle of parsimony, CONTIN approximates a solution to the inverse Laplace transform applied to the decay of peak intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 34 publications
4
66
1
1
Order By: Relevance
“…For the NOM, CONTIN, which can deal with continuous distributions of diffusivities, is the most appropriate when the overall distribution of diffusion coefficients is required. Morris et al 57 carried out a detailed study on humic materials and demonstrated the application of CONTIN to probe the polydispersivity of humic material. However, the drawback associated with CONTIN is that it tends to 'over-smooth' the diffusion data and separation is rarely observed in the 2-D DOSY plot for NOM.…”
Section: Understanding the Structures And Aggregation Of Nommentioning
confidence: 99%
See 1 more Smart Citation
“…For the NOM, CONTIN, which can deal with continuous distributions of diffusivities, is the most appropriate when the overall distribution of diffusion coefficients is required. Morris et al 57 carried out a detailed study on humic materials and demonstrated the application of CONTIN to probe the polydispersivity of humic material. However, the drawback associated with CONTIN is that it tends to 'over-smooth' the diffusion data and separation is rarely observed in the 2-D DOSY plot for NOM.…”
Section: Understanding the Structures And Aggregation Of Nommentioning
confidence: 99%
“…8(F)]. It may be possible to extract semiquantitative information from such projections 57 and in this example it is clear that even with a WS-FSFA/Cd ratio as small as 1 : 20 by weight, the majority of the Cd ions undergo exchange to some extent with the WS-FSFA components. Such findings have strong implications for understanding the behavior and toxicity of cadmium in the environment.…”
Section: Probing Nom Interactions By Diffusion Order Spectroscopymentioning
confidence: 99%
“…[106] As discussed by Simpson, [47] there are different methods to process DOSY spectra. The CONTIN technique was introduced by Morris et al [107] in NOM studies as a means to solve the inverse of the Laplace transform and provide a distribution of diffusivities for a number of soil fulvic acid and HA. [107,108] Thus, for mixtures containing NOM and a contaminant, DOSY-NMR has the potential to map the changes in diffusion of both the contaminant and the surrounding molecules, thus providing a direct evidence of the occurred interactions.…”
Section: Molecular Diffusionmentioning
confidence: 99%
“…The CONTIN technique was introduced by Morris et al [107] in NOM studies as a means to solve the inverse of the Laplace transform and provide a distribution of diffusivities for a number of soil fulvic acid and HA. [107,108] Thus, for mixtures containing NOM and a contaminant, DOSY-NMR has the potential to map the changes in diffusion of both the contaminant and the surrounding molecules, thus providing a direct evidence of the occurred interactions. [98] However, analogously to relaxation parameters, also in case of self-diffusion, one has to take into account that the self-diffusion measured by DOSY-NMR corresponds to an intermediate value between those of both the free and bound ligands.…”
Section: Molecular Diffusionmentioning
confidence: 99%
“…NMR is a valuable tool for the quantitative analysis of mixtures of organic compounds covering a wide range of molecular sizes such as humic substances (1)(2)(3) or mineral oils (4). In these systems, NMR delivers results unobtainable by other spectroscopic or chemical techniques.…”
Section: Introductionmentioning
confidence: 99%